Інформаційний аналіз в інтродукційних дослідженнях - Zaitseva, I.О. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Possibilities of using informational mathematical approach to integral estimate of plants' introduction success are under consideration. According to the results of complex analysis of oxidative processes and proteincarbohydrates metabolism in 20 species of genus Deutzia Thunb., Hydrangea L., Philadelphus L., Syringa L., introduced in the Steppe Dniepro region, the informational probabilisticstatistical indices were evaluated. These indices were entropy, orderliness of biosystems' and information redun dance coefficient. They were used as criteria of a measure reliability of plants' functioning under con ditions of the introduction area. Methodology of quantitative estimation of complexity of biosystems' organization and its informational characteristics are presented.